Resection of Orbital Myxoma With Magnetic Resonance Imaging Evidence of Ethmoid Sinus Origin: Case Report and Review of 20 Patients in the Literature - Toshihiko Matsuo MD, PhD; Takehiro Tanaka MD, PhD (SAGE Publishing, 2023)
A 41-year-old woman showed a palpable mass at the superonasal orbital edge on the right side. Magnetic resonance imaging demonstrated a lobulated fluid-containing tubular mass which extended anteriorly to posteriorly along the medial orbital wall, nasal to the eyeball. She was followed once a year for 8 years until the age of 49 years when she decided to undergo surgical resection because of the enlarged mass. The lobulated large mass was resected and the pathology showed sparsely distributed spindle cells, positive for CD34, in alcian blue-positive mucous substances, indicative of myxoma. Postoperative magnetic resonance imaging showed residual lobulated tubular mass along the optic nerve on the medial side and superior to the eyeball. The residual orbital mass showed stable structure with more evident connection with the ethmoid sinus lesion, suggestive of the ethmoid origin, in 12 years until the age of 61 years. In the review of 20 patients with orbital myxomas in the literature, in addition to this case, roughly classified locations in the orbit were retrobulbar in 8 patients, on the lateral side of the orbit in 4, on the superior side in 6, on the medial side in 1 (this patient), and in the orbit with no specific description in 2. In pathological examinations, immunohistochemistry was not done in 8 patients, done but all negative in 2, and positive in 11 patients: nerve sheath myxoma was diagnosed in 3 patients based on positive S100 staining. Orbital myxoma is rare but considered in differential diagnosis of orbital masses.